Validation of the oral health impact profile applied to patients with periodontal disease - Moral-de la Rubia, José; Rodríguez-Franco, Norma Idalia (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the metric properties of the Oral Health Impact Profile applied to Periodontal Disease (OHIP-14-PD) have not been properly studied and questions remain about the factor structure of OHIP-14. The objectives of the present study were to analyze the distribution, discriminability, and internal consistency of the items and total score of the OHIP-14-PD, prove their discriminant validity to differentiate between periodontal and gingivitis patients, explore their factor structure, and contrast several factor models proposed for the OHIP-14, determining the internal consistency and the convergent and discriminant validity of its factors. Methods: a non-probabilistic sample was gathered including 249 adult dental patients in the city of Monterrey (Mexico). Results: the internal consistency of the 14 items was very high (ordinal α = 0.928). The distribution of the total score showed asymmetry and positive kurtosis, i.e. concentration in low scores. The central tendency of periodontal patients was significantly higher than that of gingivitis patients. The exploratory factor analysis yielded two models: one with one factor, and one with three factors (physical impact [items 1 to 4 and 7], physical disability [items 5 and 6] and psychosocial impact [items 8 to 14]). The hierarchical factor models proposed for the OHIP-14 showed standardized parameters outside the range of allowable values. Conclusions: The OHIP-14-PD has internal consistency and discriminant validity. The one-factor model is the best model. Its adjustment improves by specifying a correlation between the residuals of the two items corresponding to the physical disability factor.